2012
DOI: 10.1016/j.jmb.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Basis of the Binding of WWOX Tumor Suppressor to WBP1 and WBP2 Adaptors

Abstract: The WWOX tumor suppressor participates in a diverse array of cellular activities by virtue of its ability to recognize WBP1 and WBP2 signaling adaptors among a wide variety of other ligands. Herein, using a multitude of biophysical techniques, we provide evidence that while the WW1 domain of WWOX binds to PPXY motifs within WBP1 and WBP2 in a physiologically-relevant manner, the WW2 domain exhibits no affinity toward any of these PPXY motifs. Importantly, our data suggest that while R25/W44 residues located wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(94 citation statements)
references
References 57 publications
10
81
3
Order By: Relevance
“…Intriguingly, complexes pulled down via GST-WW1,2 were much less than those by GST-WW1 alone, suggesting that WW2 might have an inhibitory effect on the interaction ability of WWOX. In agreement with these observations, McDonald et al (37) FIGURE 6. ITCH mediates Lys-63-linked polyubiquitination of WWOX.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Intriguingly, complexes pulled down via GST-WW1,2 were much less than those by GST-WW1 alone, suggesting that WW2 might have an inhibitory effect on the interaction ability of WWOX. In agreement with these observations, McDonald et al (37) FIGURE 6. ITCH mediates Lys-63-linked polyubiquitination of WWOX.…”
Section: Discussionsupporting
confidence: 74%
“…This impaired ability was suggested to be due to the presence of Glu-66/Tyr-85 residues within the WW2 domain binding pocket as compared with Arg-25/Trp-44 within the WW1 domain. Introduction of an E66R/Y85W double substitution within the WW2 domain of WWOX results in gain of function and restores binding to WBP1 and WBP2 (37). Furthermore, the Y85W substitution within the WW2 domain restores its binding to PPXY motifs of ErbB4 in a manner very similar to the binding of the WW1 domain of WWOX.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, Wwox was thought to belong to Group I after demonstrating binding of proteins harboring PP x Y motifs (where P is proline, Y is tyrosine and x is any amino acid) through its first WW domain. 4,5,6 However, a recent study by Abu-Odeh et al employed an MS-based screen which confirmed previous PP x Y protein interactions, but also demonstrated that the majority of Wwox interacting proteins did not contain PY motifs. 7 Rather, these proteins exhibited PP x F or LP x F motifs (where F is phenylalanine and L is leucine), suggesting that perhaps WW1 domain of WWOX binds non-canonical proline-rich motifs.…”
Section: Introductionmentioning
confidence: 61%
“…5,6,7 After showing that the second WW domain, WW2, contains two distinct amino acid residues within the WW binding pocket, compared to WW1, McDonald et al proposed that the WW2 domain serves as a chaperone for augmenting physiological binding of WW1. 4 …”
Section: Introductionmentioning
confidence: 99%
“…WBP2 can activate the ER transactivation pathway and promote cell proliferation. WWOX physically interacts with WBP2 and suppresses ER transactivation pathways 48,49 ( Figure 1). Thus, loss of WWOX expression can result in tamoxifen resistance by up-regulating ER and Her2 transcriptional activities.…”
Section: Loss Of Wwox Correlates With Resistance To Endocrine Therapymentioning
confidence: 99%